2020
DOI: 10.3390/ijms21217896
|View full text |Cite
|
Sign up to set email alerts
|

High Sensitivity In Vivo Imaging of Cancer Metastasis Using a Near-Infrared Luciferin Analogue seMpai

Abstract: Bioluminescence imaging (BLI) is useful to monitor cell movement and gene expression in live animals. However, D-luciferin has a short wavelength (560 nm) which is absorbed by tissues and the use of near-infrared (NIR) luciferin analogues enable high sensitivity in vivo BLI. The AkaLumine-AkaLuc BLI system (Aka-BLI) can detect resolution at the single-cell level; however, it has a clear hepatic background signal. Here, to enable the highly sensitive detection of bioluminescence from the surrounding liver tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 18 publications
(28 reference statements)
1
23
0
Order By: Relevance
“…Two characteristics of TokeOni were improved by seMpai; since the pH value of TokeOni is acidic [ 89 ], acidosis is a potential problem, and hepatic background signals are detected when using TokeOni [ 89 , 106 ] but not when using DLH2. Furthermore, seMpai is a luciferin analogue designed with containing N-atom in the AkaLumine moiety, slightly changing its bioluminescence reaction with Fluc and AkaLuc ( K m = 6.2 and 44.9 µM, respectively in Table 2 ).…”
Section: Chemical and Physical Characteristics Of The Nir Luciferimentioning
confidence: 99%
See 2 more Smart Citations
“…Two characteristics of TokeOni were improved by seMpai; since the pH value of TokeOni is acidic [ 89 ], acidosis is a potential problem, and hepatic background signals are detected when using TokeOni [ 89 , 106 ] but not when using DLH2. Furthermore, seMpai is a luciferin analogue designed with containing N-atom in the AkaLumine moiety, slightly changing its bioluminescence reaction with Fluc and AkaLuc ( K m = 6.2 and 44.9 µM, respectively in Table 2 ).…”
Section: Chemical and Physical Characteristics Of The Nir Luciferimentioning
confidence: 99%
“…Moreover, seMpai allows high-sensitivity detection in in vivo BLI, and it can be used to detect pulmonary micro-metastases. In addition, seMpai is highly soluble (69 mM) in PBS (pH 7.4) [ 82 ] and does not produce hepatic background signals in breast cancer metastasis models [ 89 ]. However, seMpai BLI cannot detect biological events at single-cell-level resolutions, like AkaBLI.…”
Section: Chemical and Physical Characteristics Of The Nir Luciferimentioning
confidence: 99%
See 1 more Smart Citation
“…Optical techniques are subject to attenuation at depth due to absorption and scattering of light, and thus superficial tumors are most easily detected, specifically subcutaneous, or at disease sites near the surface such as mammary fat pad (Figure 3). However, light can penetrate several millimeters and effective signal is observed by BLI in deeper tissues such as the lungs [180,[187][188][189], prostate [190][191][192], brain [193,194], pancreas [195,196], liver [197,198], head and neck [113], bone [199,200] and kidney [136,201] in mice. The most common implementation of BLI in oncology is simply to relate signal intensity to tumor burden and indeed several studies have shown that there is a strong correlation for untreated control tumors up to about 2 cm 3 [89,202].…”
Section: Atp + D-luciferin + O2 -----------Luciferase ---------------mentioning
confidence: 99%
“…seMpai (29b) was developed to improve two weak points in TokeOni: neutral pH and disturbance by hepatic background signals. As TokeOni is acidic [43], it may cause acidosis when injected; moreover, TokeOni detects the hepatic background signals, which are not detected by LH2 [43,44]. Due to the effect of N atom, seMpai was sufficiently soluble for administration to experimental animals and 69 mM was dissolved in phosphate buffered saline (pH 7.4) [40].…”
Section: Bli With Sempaimentioning
confidence: 99%